2014
DOI: 10.5603/kp.a2013.0285
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, management and five-year outcomes of patients with high risk, stable multivessel coronary heart disease

Abstract: Our study showed that patients with advanced MCAD who are qualified for complete surgical revascularisation benefitted more with regard to several primary end points at five-year follow-up than those who were not qualified for surgery and who were treated with medical therapy supplemented in selected cases with incomplete percutaneous revascularisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Degawa-Yamauchi et al [14] found a weak correlation between plasma serum resistin and BMI, whereas Silha et al [15] reported that resistin concentrations were not correlated with BMI, although the concentrations were correlated significantly with HOMA-IR. Furthermore, Kręcki et al [16] did not observe any correlation between MACE and resistin levels, whereas Momiyama et al [17] showed a correlation with resistin levels higher than 4.0 ng/mL with MACE in patients undergoing elective PCI.…”
Section: Discussionmentioning
confidence: 93%
“…Degawa-Yamauchi et al [14] found a weak correlation between plasma serum resistin and BMI, whereas Silha et al [15] reported that resistin concentrations were not correlated with BMI, although the concentrations were correlated significantly with HOMA-IR. Furthermore, Kręcki et al [16] did not observe any correlation between MACE and resistin levels, whereas Momiyama et al [17] showed a correlation with resistin levels higher than 4.0 ng/mL with MACE in patients undergoing elective PCI.…”
Section: Discussionmentioning
confidence: 93%
“…Approximately 50% of all deaths are caused by CAD. Hence, it is crucial to identify patients with CAD [1][2][3]. Prediction of cardiovascular disease in the adult population is very important in terms of both prevention and treatment.…”
Section: Introducti̇onmentioning
confidence: 99%
“…The technique of a "buddy wire" was described both in the case of difficult procedures on coronary vessels and the facilitation of the introduction of trans-septal sheaths through the frail interatrial septum [8][9][10].…”
Section: Discussionmentioning
confidence: 99%